Removal of arsenate from aqueous solution by nanocrystalline Mg/Al layered double hydroxide : sorption characteristics, prospects, and challenges - Goh, Kok Hui (2012)
Removal of arsenate (As(V)) from aqueous solution using both nanocrystalline and coprecipitated Mg/Al layered double hydroxides (LDHs) was examined under different sorption/desorption conditions. The surface area, pore volume, and pore size of the nanocrystalline LDH were significantly higher than those of the coprecipitated LDH, thus resulting in a higher As(V) sorption maximum than the coprecipitated LDH. The calculated activation energy (Ea) value was 24.7 kJ/mol, suggesting the occurrence of anion exchange process for As(V) removal by the nanocrystalline LDH. The predominance of anion exchange process was further supported by the investigation of ionic strength effect, and XRD and FTIR analyses. The effect of aqueous matrix on As(V) sorption by the nanocrystalline LDH was found to increase in the order of nitrate < silica < sulfate < carbonate < phosphate. Regeneration study showed that a secondary sorption mechanism might occur concurrently for the As(V) sorption by nanocrystalline LDH besides the predominant anion exchange process. Prospects and challenges for practical application of the nanocrystalline LDH were also discussed in the latter part of this study.